Relative humidity and temperature impact to ozone and nitrogen oxides removal rate in the experimental chamber - Valuntaitė, Vaida; Šerevičienė, Vaida; Girgždienė, Raselė; Paliulis, Dainius (Journal of Environmental Engineering and Landscape Management, 2012)
The indoor ozone and nitrogen oxides concentration depends on their outdoor concentrations, indoor sources and their removal rates on the surfaces. The paper presents experimental data of the of ozone and nitrogen oxide removal in the chamber. The ambient conditions were simulated by four combination of different temperature and relative humidity levels. The impact of temperature (T = 20 °C and T = 30 °C) and relative humidity (RH = 24% and RH = 80%) on the deposition velocity was estimated. It was found that the ozone removal in the chamber was influenced more by temperature, and the nitrogen oxides removal was affected more by relative air humidity. The results showed that higher ambient temperature (T = 30 °C) increased the ozone removal rate in the chamber 3 times on an average, and high relative humidity (RH = 80%) increased the NOx removal rate 4.5 times in comparison with the initial conditions (T = 20 °C; RH = 24%). The obtained deposition velocities varied in the range (0.0045–0.0137) cm s−1 for ozone and in the range (0.002-0.0129) cm s −1 for nitrogen dioxide.Article in English.Santykinio oro drėgnio ir temperatūros įtaka ozono ir azoto oksidų suirimo greičiui eksperimentinėje kamerojeSantrauka. Ozono ir azoto oksidų koncentracija patalpose priklauso nuo šių teršalų koncentracijos lauke, jų šaltinių patalpose ir šių teršalų suirimo greičio ant skirtingų paviršių. Darbe nagrinėjamas ozono ir azoto oksidų suirimas eksperimentinėje kameroje. Skirtingos mikroklimatinės sąlygos buvo sukuriamos naudojant keturių skirtingų temperatūrų ir santykinių oro drėgnių lygių derinius. Vertinta temperatūros (T = 20 °C ir T = 30 °C) ir santykinio drėgnio (RH = 24 % ir RH = 80 %) įtaka tiriamų teršalų suirimui. Nustatyta, kad ozono suirimui daugiau įtakos turėjo temperatūra, o NOX irimui – santykinis oro drėgnis. Nustatyta, kad aukštesnė aplinkos temperatūra (T = 30 °C) paspartina ozono suirimą kameroje vidutiniškai tris kartus, o didelis santykinis drėgnis (RH = 80 %) paspartina NOX suirimą 4,5 karto, lyginant su pradinėmis sąlygomis (T = 20 °C; RH = 24 %). Eksperimento metu ozono suirimo greitis kito nuo 0,0045 iki 0,0137 cm s−1, o azoto oksidų – nuo 0,002 iki 0,0129 cm s−1.Reikšminiai žodžiai: ozonas, azoto oksidai, santykinis oro drėgnis, temperatūra, kamera, suirimo greitisВлияние относительной влажности и темпера туры нас корость распада озона и оксидов азота в экспериментальной камереРезюме. Концентрации озона и оксидов азота в помещениях зависят от их концентрации в открытом воздухе, источникахвнутри помещений и скорости их распада на поверхностях. В статье представлены экспериментальные данные по распаду озона и оксидов азота в камере при разных микроклиматических условиях, созданных с применением четырех комбинаций температур и относительной влажности. Оценивалось воздействие температуры (T = 20 °С и Т = 30 °С) и относительной влажности воздуха (RH = 24% и RH = 80%) на скорость осаждения. Было обнаружено,что на распад озона в камере большее влияние оказывает температура, а на распад оксидов азота – относительная влажность воздуха. Результаты показали, что при повышении температуры окружающей среды (T = 30 °С) увеличилась скорость распада озона в камере в 3 раза по сравнению со средней, а при высокой относительной влажности (RH = 80%) увеличилась скорость распада NOx в 4,5 раза по сравнению с начальными условиями (T = 20 °C; RH = 24%). Полученные для озона скорости осаждения варьировали в пределах (0,0045−0,0137) cм с-1, а для оксида азота – в пределах (0,002−0,0129) cм с-1.Ключевые слова: озон, оксиды азота, относительная влажность, температура, камера, скорости осаждения